Fiqih Munakahat Dalam Pendidikan Islam - Mega Utami Imyansah; Indah Mutia; Deta Rehulina; Naura Azifa; Putri Adillah; Wismanto Wismanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Fiqh mukahat in Islamic education is an important aspect that focuses on ethics and behavior in the learning environment. This article discusses the importance of munakahat education and its implications in creating a sakinah family. There are several theme s that will be discussed, including: analysis of the objectives and concepts of munakahat education, and the implementation of munakahat education in realizing a sakinah family, Fiqh mukahat provides guidelines for students and educators to develop quality character, promote mutual understanding, and create a harmonious learning environment. A deep understanding of the principles of mukahat fiqh can help create an enlightening generation that reflects Islamic values in their daily lives. In this study the author uses qualitative methods based on library research referenced through journals, as well as books.